Unix Filesystems - Evolution, Design And Implementation - Pate, Steve D. (Wiley Publishing, 2011)
Covers all versions of UNIX, as well as Linux, operating systems that are used by the majority of Fortune 1000 companies for their mission-critical data Offers more detail than other books on the file input/output aspects of UNIX programming Describes implementation of UNIX filesystems over a thirty year period Demonstrates VERITAS and other filesystem examples